VD_FINDINFO HC / 2012 / 732 vom 15. November 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 176 CC, 117 let. b CPC (CH), 312 al. 1 CPC (CH), 317 CPC (CH)